PENGARUH INDEPENDENSI, PROFESIONALISME, STRUKTUR AUDIT, DAN ROLE STRESS TERHADAP KINERJA AUDITOR BPK RI PERWAKILAN PROVINSI BALI - Bandar Wira Putra, I Gede (E-Jurnal Akuntansi, 2012)
ABSTRACT Financial management supervision should do well for the success of national development. The rise of cases of deviation from the state budget makes BPK RI demanded better performance. The purpose of this study is to know the influence of the independence, professionalism, audit structure, role conflict and role ambiguity on auditor BPK RI Perwakilan Provinsi Bali performance. The analysis techniques used is multiple linear regression. The population were 41 auditors of BPK RI Perwakilan Provinsi Bali. The results showed variable independence and audit structures significantly positive effect on auditor performance, role conflict variables significantly negative effect on auditor performance, while the role of professionalism and role ambiguity are not shown affect the auditor performance. Keywords : independence, profesionalism, audit structure, role conflict, role ambiguity, and auditor performance.
Keywords: independence, profesionalism, audit structure, role conflict, role ambiguity, and auditor performance.